Morphological characterization of canine retrobulbar lymphoma - Natthanet Sritrakoon (Open Veterinary Journal, 2018)
This report characterized seven cases of canine retrobulbar lymphoma that have been diagnosed during 2008 to 2014 by immunophenotyping of CD3 and Pax5. Classification of lymphoma were performed according to the revised WHO guidelines. Four retrobulbar lymphomas were of T-cell origin, while the others were of B-cell. Out of 7 cases, four subtypes were diagnosed in this study; T-cell-rich large B-cell lymphoma (3/7), T-cell lymphoblastic lymphoma (2/7), peripheral T-cell lymphoma (1/7), and cutaneous nonepitheliotropic lymphoma (1/7). T-cell-rich large B-cell lymphoma was found to be the most frequent subtype found.